Pengaruh Produk, Harga, Bahan Baku Bagi Penjualan Di PT. Hon Chuan Indonesia Periode 2015-2019 - Yeni; Hartelina; Didit Supriadi; DJ Suyaman (Coopetition : Jurnal Ilmiah Manajemen, 2021)
The increasing of plastic industry growth in Indonesia have bump-up potential of plastic pellets requirement as well, which the nature source of plastic pellets itself restricted and limited. Those will impact to plastic pellets import high demand especially for food and beverages area who use them. Strict competition and challenges to the restriction of plastic raw material usage need attention on product, price, raw material, and impact to the sales. The purpose of this study was to describe of product, price, raw material, and impact to sales, analyze the correlation value and the effect among them. This study was conducted use quantitative research method with descriptive approach and survey method. This study conducted in PT. Hon Chuan Indonesia with 118 respondents as representative from their customer data. Based on research result marketing strategy, product, price, raw material, and sales was in approve category descriptively. And it has 1) a fairly strong and strong correlation range between product and price, 2) significant positive partially effect between product, price, and raw material 3) simultaneously effect between product, price, and raw material 4) influence between raw material and sales.